Interferon lambda 4 genotypes and resistance‐associated variants in patients infected with hepatitis C virus genotypes 1 and 3. Issue 1 (25th November 2015) - Peiffer, Kai‐Henrik; Sommer, Lisa; Susser, Simone; Vermehren, Johannes; Herrmann, Eva; Döring, Matthias; Dietz, Julia; Perner, Dany; Berkowski, Caterina; Zeuzem, Stefan; Sarrazin, Christoph
Abstract : Single‐nucleotide polymorphisms (SNPs) in the interferon lambda 4 ( IFNL4 ) gene are predictors for treatment success in patients with hepatitis C virus (HCV) infection. For direct‐acting antiviral combinations only weak association with IFNL4 SNPs was observed. Little is known about potential selections of resistance‐associated variants (RAVs) by the IFNL4 genotype. This study analyzed the prevalence of RAVs to currently approved direct‐acting antivirals in a large European population in correlation to SNPs in IFNL4 . Samples of 633 patients chronically infected with HCV genotypes 1a (n = 259), 1b (n = 323), and 3 (n = 51) were genotyped for rs12979860 (formerly known as IL28B ) and rs368234815. RAVs in NS3, NS5A, and NS5B were detected by population‐based sequencing. In addition, IFNL4 SNPs and NS5A RAVs were analyzed including deep sequencing (n = 109) in an independent replication cohort of HCV genotype 1‐infected patients (n = 201). No significant correlation was found between IFNL4 SNPs and rare and common RAVs within NS3 and NS5B . In contrast, the NS5A RAV Y93H was detected frequently in HCV genotype 1b (14%) and significantly associated with the beneficial IFNL4 SNPs ( P < 0.001 and P = 0.002, respectively). Moreover, the presence of Y93H in HCV genotype 1b patients was significantly associated with the second site variant T83M ( P < 0.001). Independent factors significantly associated with the presence of Y93H were IFNL4 genotype and high baseline viral load. Conclusion: The NS5A RAV Y93H is significantly associated with the presence of beneficial IFNL4 SNPs and a high baseline viral load in HCV genotype 1‐infected patients, which may explain a lack of correlation or even an inverse correlation of treatment response with IFNL4 genotype in some NS5A inhibitor containing IFN‐free regimens. (Hepatology 2016;63:63–73)